Carbon quantum dots for sustainable energy and optoelectronics - Batabyal, Sudip Kumar (Woodhead Publishing, an imprint of Elsevier, 2023)
Carbon Quantum Dots for Sustainable Energy and Optoelectronics reviews the synthesis, properties, and applications of carbon nanodots. This book provides readers with an overview of the key advances in the development of carbon quantum dots including synthesis and surface engineering strategies such as pyrolysis-based synthesis, biomass-based synthesis, functionalization, and other methods toward large-scale development of these carbon nanomaterials. The emerging applications of carbon quantum dots in different fields, such as energy harvesting, energy storage, and biomedical applications, are thoroughly reviewed, emphasizing the impact of enhanced properties of carbon quantum dots for these applications. Carbon Quantum Dots for Sustainable Energy and Optoelectronics is suitable for graduate students, materials scientists, and engineers working in academia and industry. This book is also beneficial for the interdisciplinary community of researchers and practitioners working in the field of nanotechnology. Introduces recent advances in the understanding of carbon quantum dots, including relevant synthesis and surface engineering strategies for their large-scale development Provides an overview of the most relevant applications of carbon quantum dots for the development of sustainable technologies in optoelectronics and energy storage and production Discusses future research directions and remaining challenges towards the commercial translation of carbon quantum dots.
Keywords: Quantum dots -- Industrial applications.; Optoelectronics.; elektronické knihy; electronic books